Unraveling the Roles of La Substitution for Different Transition Metals on P2-Na0.67Mn0.6Ni0.2Co0.2O2 Cathode Materials. Issue 16 (25th November 2020) - Wang, Huibo; Li, Ling; Han, Wenze; Guo, Hao; Sun, Limei; Liu, Xiangfeng
Abstract : P2-type layered transitional metal oxides as the promising cathode materials for sodium-ion batteries (SIBs) have attracted great attention. But their poor cycling stability and inferior rate capability restrict the practical applications. Foreign elements doping has been considered as one effective strategy to overcome these shortcomings. But the roles of the dopants are still poorly understood. Herein, we have taken La doping to modulate the crystal and electronic structure, and systematically investigated the different effects of La substitution for Mn, Ni and Co on the structure and electrochemical properties of P2-Na0.67 Mn0.6 Ni0.2 Co0.2 O2 cathode materials. The substitution of La reduces Mn 3+ in the crystal lattice which alleviates Jahn−Teller distortion and reduces the collapse of the transition metal layer caused by the dissolution of Mn 3+ . Due to the large La–O bonding energy, the substitution of La for Mn, Ni and Co shortens O–O and TM–O bond length, and the thickness of TMO2, which all enhance the structure stability. In addition, the substitution of La for Mn, Ni and Co also expands the interlayer spacing and Na–O bond length enhancing Na + diffusion kinetics. The substitution of La for Mn shows better rate capability and cycling stability than the substitution for Ni and Co. It can provide a discharge capacity of 86 mAh g −1 at a high current density of 8C (1600 mA g −1 ) with a capacity retention rate of 95%. This study also presents some insights into modulating the lattice and electronic structure by elements doping to optimize the electrochemical performances.